BAMBU DENGAN BERBAGAI MANFAATNYA - K. Widnyana (Environmental Research Center (PPLH) of Udayana University, 2008)
Bamboo during the time less get existence cause that assumed did not be important. This ascription cause that bamboo did not become the high economic valuable kommodity for society. During the time rehabilitations of the critical farm and forest area almost everything use the crop tree and next to nothing bamboo cultivation. Studies indicate that one hectare of bamboo crop can permeate more than 12 ton CO2 from the air. Bamboo also more effective in conservation irrigate where permeable bamboo 90% rainwater, while tree only 35 - 40%. Management and good bamboo crop can improve the society economics. Young bamboo can be used for the vegetable of bamboo bar and for the requirement of industrials, construction material, and crafts. If cycling enterpasing of bamboo forest during 20 year, hence total fund requirement reach the Rp 87.960.100,00 per ha with the acquirement [of] result of equal to Rp 767.520.000,00. Thereby the effort competent bamboo cultivation visible and profit.